Zakat Institution of Financial Transparency Model: An Explanatory Research - Wahyudi, Muhamad; Huda, Nurul; Herianingrum, Sri; Ratnasari, Ririn Tri (ZISWAF, 2021)
Public demand for financial transparency of zakat institutions is getting stronger. The weak quality of financial reports resulted in a distrust of this institution. Therefore, a framework is needed as a reference in compiling and presenting quality financial reports that meet public expectations. This article aims to propose a financial transparency framework for the Amil Zakat Institution (LAZ) in Indonesia. This is a descriptive qualitative study with an explanatory approach. Furthermore, data collection was carried out through studies related to financial transparency of the institution and was complemented by interviews with directors, distribution managers, accounting staff, and three muzaki of zakat institutions in Central Java. The results concluded that the framework for transparency practice in the financial statements of zakat institutions comprises three parts, namely the principle of tauhid as a foundation component. Amil zakat's professionalism, internal audit, internal control, and financial accounting standards are the principal components, as well as the use of the website as support. The implication of this study is that the credibility of zakat institutions can be increased by improving the quality of financial reports.